Technology Entrepreneurship Project (ENT 600) : Summit Company [Malaysia] Sdn. Bhd. / Afiqah Nadzirah Ariffin - Ariffin, Afiqah Nadzirah (2021)
This assignment is an attempt in order to expose to students about entrepreneurship. From this subject, students can know how to practice the theories that have been learnt. In this assignment, students are required to do a research about one chosen company. My chosen company is Pureen which is a company that produce mainly baby stuffs. In the first part of the report, I have to do some research about the company background and collect the needed information. The needed information is about the company background, business strategy, marketing strategy and operational strategy. In another part of this assignment, I have to construct a SWOT analysis table. By doing the analysis, I am able to identify the strengths, weaknesses, opportunities and threats of the company. By gaining that information, I am able to recommend some improvements regarding the product.